Effect of Jatropha methyl ester on waste plastic oil fueled DI diesel engine. Issue 4 (November 2016) - Senthilkumar, P.; Sankaranarayanan, G.
Abstract: Rapid demanding of conventional fossil fuels, increasing costs and environmental issues is the major problems for a substitute fuel. On the other hand waste plastic poses a very serious environmental challenges because of their disposal problems all over the world. The oil obtained by pyrolysis of waste plastics can be utilized as an alternate fuel for diesel engine without any modifications to the engine which results, increase the emissions like carbon monoxide (CO) and oxides of nitrogen (NOx ) and Hydrocarbons (HC) compared with diesel. In this present study, the waste plastic oil mixed with 10% vol and 20% vol of Jatropha methyl ester (JME) oil used as fuel for the DI diesel engine and the combustion, performance and emission characteristics were studied. The experimental results indicated that the brake thermal efficiencies of waste plastic oil–JME blends at full load conditions are higher as compared to that of waste plastic oil. BTE increased by about 2.24% with PJ20 operation at full load compared to waste plastic oil. The Brake specific fuel consumption (BSFC) increases with an increase in the JME blend ratio and decreases with an increase in engine load. The CO and HC emissions were decreased with increase in percentage of JME in waste plastic oil blends. HC and CO emissions for PJ20 operation are about 11 ppm and 0.13% lower than waste plastic oil at full load respectively. The NOx emission was slightly increased with increase in percentage of JME in waste plastic oils. NOx emission is 20 ppm higher for PJ20 operation than waste plastic oil. Smoke emission decreased by about 11.4% in the case of PJ20 compared to waste plastic oil. Highlights: Obtained waste plastics oil through pyrolysis process and utilized as a DI diesel engine fuel. Aspects of waste plastic oil–Jatropha methyl ester blends used as an alternate fuel in diesel engine. Reduction of emission of hazardous gases in conventional DI diesel engines and enhances the DI engine performance.